IMF Survey magazine - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 1995)
the IMF Survey, provides topical coverage of the IMF's activities, policies, and research in the context of global economic and financial developments
Is published in English, French and Spanish 23 times/year plus an annual index and an annual IMF Survey Supplement. Few issues from vol 36 (2007) and 37 (2008) are also available at the library
Keywords: International banking; FOREIGN EXCHANGE; PERIODICALS; INTERNATIONAL BANKING